2018
DOI: 10.1016/j.neo.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Reversal Promotes Cancer Stem Cell-Like Cell Formation

Abstract: It has long been a puzzle in cancer treatment that despite the initial appearance of apoptosis, the process could be reversed in some cancer cells and often results in more aggressive tumors and metastasis. The mechanism for this recurrence is yet unknown. Here we report that human mammary carcinoma cells induced to undergo apoptosis could recover with increased tumorigenicity in vitro and in vivo, and induced lymph node metastasis. Specifically, the reversed cells underwent epithelial-to-mesenchymal transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 40 publications
1
40
0
1
Order By: Relevance
“…However, most metastatic cancers, including lung, brain, skin and pancreatic cancers, inevitably recur, leading to treatment failure [ 185 189 ]. Anastasis has been observed in various cultured human cancer cell lines including cervical cancer, small cell lung carcinoma, neuroblastoma, skin cancer, testicular cancer, liver cancer, breast cancer and prostate cancer [ 21 , 26 , 28 , 29 , 31 33 , 85 ], thereby suggesting that this process could be a common occurrence in cancers. Furthermore, upregulation of genes involved in cell migration (MMP9, MMP10 and MMP13) and angiogenesis (ANGPTL4, ANGPT2 and VEGFA) during anastasis [ 29 ] suggests a plausible connection between anastasis and cancer metastasis during a recurrence.…”
Section: Looking Forwardmentioning
confidence: 99%
“…However, most metastatic cancers, including lung, brain, skin and pancreatic cancers, inevitably recur, leading to treatment failure [ 185 189 ]. Anastasis has been observed in various cultured human cancer cell lines including cervical cancer, small cell lung carcinoma, neuroblastoma, skin cancer, testicular cancer, liver cancer, breast cancer and prostate cancer [ 21 , 26 , 28 , 29 , 31 33 , 85 ], thereby suggesting that this process could be a common occurrence in cancers. Furthermore, upregulation of genes involved in cell migration (MMP9, MMP10 and MMP13) and angiogenesis (ANGPTL4, ANGPT2 and VEGFA) during anastasis [ 29 ] suggests a plausible connection between anastasis and cancer metastasis during a recurrence.…”
Section: Looking Forwardmentioning
confidence: 99%
“…Time-lapse live cell microscopy has demonstrated that cancer cell fragments resulting from the formation of apoptotic bodies can coalesce to give rise to cells with apparently normal morphology, often displaying an increased number of micronuclei and chromosomal abnormalities that can lead to increased aneuploidy [125,127]. Consistent with these observations, studies have revealed that anastatic cancer cells acquire stem cell-like properties that can promote tumor progression, therapy resistance, and disease recurrence [125][126][127]130].…”
Section: Recovery Of Apoptotic Cancer Cells From the Brink Of Deathmentioning
confidence: 88%
“…Failure to execute apoptosis also seems to impact the emergence of cancer stem cell-like cells (CSCs) in breast cancer. Here the authors found that breast cancer cells surviving non-lethal doses of staurosporine gain in metastatic potential in vivo while some of them acquired CSCs properties 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Even though we used melanoma cancer cells as a proof-of-principle tool to investigate failed apoptosis, we hypothesize that our findings might extend to other types of cancers. In this vein, research conducted in colon or breast cancer cells also highlighted a correlation between increased aggressiveness and non-lethal caspase activation 35,48 .…”
Section: Discussionmentioning
confidence: 99%